Implementation of Discipline and Politeness Value and Their Relevancies Toward Social Attitudes of Elementary Students - Candrawati, Melinda; Atmaja, Hamdan Tri; Khafid, Muhammad (Jurnal Profesi Keguruan, 2019)
The Implementation of character value in education is important to foster the social attitude of the students to create better personalities for the sake of being human as well as good members of society. The purpose of this research is to describe and analyze the implementation of instilling discipline and polite character values toward social attitudes of the student; both inside of social study learning, and family. This research used a qualitative method. It was done at Kubangpari 01 Public Elementary School, Kersana district, Brebes Regency. The techniques of collecting data were interview, observation, and documentation. The validities of the data were source triangulation and method. The processes of analyzing data were done through data reduction, data presentation, and data conclusion/verification. The implementation of discipline character value foster into social study learning based on observation was done through initial activity before learning until it had finished. The implementation of polite character value into family life was based on training or habit to obey rules, parents’ command. Parents fostered the implementation of polite character value in family life by advising them to respect older people, to be polite and not to be rude while talking.